2016
DOI: 10.1177/1329878x16638894
|View full text |Cite
|
Sign up to set email alerts
|

For the lifestyle and a love of creativity: Australian students’ motivations for studying journalism

Abstract: A number of studies have examined why students choose to study journalism at university, but overall, this area is still relatively underexplored. Yet, understanding why students choose journalism, and what career expectations they hold, is important not only for educators but also for wider society and public debates about the future of journalism and the value of tertiary journalism education. This article examines the motivations of 1884 Australian journalism students enrolled across 10 universities. It fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 15 publications
1
22
0
5
Order By: Relevance
“…Yet the number of individuals with university degrees in the field continues to rise and currently a third of the professionals finished university level education (ibid.). This makes us go full circle to the quote by Hanusch et al (2016) that concluded the first part of this paper: Why do students enroll communication studies -by extension journalism studies? Why do they chose the program and do they at all intend to become part of the journalistic profession?…”
Section: Journalism and Journalism Education In Austriamentioning
confidence: 86%
“…Yet the number of individuals with university degrees in the field continues to rise and currently a third of the professionals finished university level education (ibid.). This makes us go full circle to the quote by Hanusch et al (2016) that concluded the first part of this paper: Why do students enroll communication studies -by extension journalism studies? Why do they chose the program and do they at all intend to become part of the journalistic profession?…”
Section: Journalism and Journalism Education In Austriamentioning
confidence: 86%
“…El cuestionario final suministrado en los tres países fue elaborado según los estándares y experiencias nacionales e internacionales en esta línea de investigación desarrolladas por Weaver y Wilhoit (1986, 1996, Weaver et al (2007), , , Ramaprasad y Kelly (2003), Mellado (2011Mellado ( , 2012, Mellado et al (2013), ) y Hanusch et al (2016. Respecto a la herramienta de origen, tomada del estudio Journalism Students Across the Globe, proyecto coordinado por Folker Hanusch y Claudia Mellado, el 21% de las preguntas en el modelo final aplicado en nuestra investigación sufrieron ciertas modificaciones consistentes en: inclusión de dos nuevas cuestiones generales, adaptación de una pregunta casi en su totalidad e incorporación de un nuevo aspecto relativo al nivel de confianza de los estudiantes en los medios de comunicación.…”
Section: Metodologíaunclassified
“…A pesar de la juventud de este campo de estudio, que obtuvo una enorme popularidad y crecimiento en todo el mundo a partir de los años 90 del siglo pasado (Deuze, 2006;Mellado et al, 2013;Hanusch et al, 2016), desde hace casi tres décadas han ido apareciendo investigaciones en todo el mundo, principalmente en el hemisferio occidental, que le han ido dando solidez y cohesión. Algunos de los principales ejemplos se encuentran en Estados Unidos y Europa con Boyd-Barrett (1970); Bowers (1974); Becker et al (1987) ;Ronneberger, 1988;Parsons (1989) ;Gaunt, 1992; el principal estudio comparativo llevado a cabo en los años noventa por Splichal y Sparks (1994); Zhu et al (1997) En estos estudios, sus investigadores indican que la educación recibida por los estudiantes de periodismo en la universidad influye en sus valores y actitudes profesionales (Splichal y Sparks, 1994;Wu y Weaver, 1998;Plaisance, 2007) y en sus procesos de socialización (Becker et al, 1987;Ronneberger, 1988;Parsons, 1989;Gaunt, 1992;Mensing, 2010).…”
Section: Cultura Periodística Pre-profesionalunclassified
See 2 more Smart Citations